2018
DOI: 10.2351/1.5038072
|View full text |Cite
|
Sign up to set email alerts
|

Complex beam profiles for laser annealing of thin-film CdTe photovoltaics

Abstract: Within the family of thin-film photovoltaics (PV), cadmium telluride has the fastest growing market share due to its high efficiencies and low cost. However, as with other PV technologies, the energy required to manufacture the panels is excessive, encompassing high environmental impact and manufacturing energy payback times of the order of 2-3 years. As part of the manufacturing process, the panels are annealed at temperatures of approximately 400 °C for 30 min, which is inherently inefficient. Laser heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Forming different structured laser beams of different wavelengths with autofocusing properties is very important in industrial applications. Such laser beams will be exploited in material processing (ablation, scribing, and annealing) [22][23][24][25][26], laser fabrication of volume (3D) structures [27,28], and optical manipulation in different mediums [29][30][31] due to its self-healing properties [32]. Moreover, we plan to extend our work on the propagation of ALBs through a turbulent media, by considering the role of amplitude of azimuthal sinusoidal phase for various values of m.…”
Section: Discussionmentioning
confidence: 99%
“…Forming different structured laser beams of different wavelengths with autofocusing properties is very important in industrial applications. Such laser beams will be exploited in material processing (ablation, scribing, and annealing) [22][23][24][25][26], laser fabrication of volume (3D) structures [27,28], and optical manipulation in different mediums [29][30][31] due to its self-healing properties [32]. Moreover, we plan to extend our work on the propagation of ALBs through a turbulent media, by considering the role of amplitude of azimuthal sinusoidal phase for various values of m.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, holographic optical elements, kinoforms which can be used to create customised laser beam profiles, have been studied by Kell et al for laser welding [26], Higginson et al for laser powder bed fusion (L-PBF) [27] and Goffin et al for wire-fed laser cladding [28] and thin-film surface annealing [29]. The majority of these studies focused on metallurgical improvements, however, Goffin et al also found that alterations in the beam profile allowed the creation of wire clad tracks with beam power requirements reduced by 30% for an enlarged gaussian beam and 50% for a square uniform beam.…”
Section: Energy Modelling In Laser Systemsmentioning
confidence: 99%
“…Laser polishing differs from more widely known techniques of laser engraving and laser ablation in that it is an equating process, no adding material or removing material as in those techniques. The profile pattern of CW laser beam from the laser generator is Gaussian beam instead of top-hat beam, where the spot is circular but with a uniform intensity profile [7]. A Gaussian beam results in a non-uniform process that polishes some areas of the panel more effectively than others, due to the differences in their thermal cycles.…”
Section: Cw Laser Beam Profile Patternmentioning
confidence: 99%